The Effect of Seating Management on Students' Motivation and Learning Outcomes for Social Studies Subject Class V at MI Somba Opu District, Kab. Gowa (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2022)
This study aims to determine the significant effect of seating management on the motivation and learning outcomes of students in Social Studies subject in class V at MI Somba Opu District, Gowa Regency. This type of research is quantitative research with True Experiment Design with pre-test, post-test control group design. The population of this study was MI Somba Opu District. The samples in this study were students of Class V at MI Madani Alauddin and MI Ash Salihin, Gowa Regency, totaling 50 students. The data collection technique used is the provision of questionnaires and taking student learning test results, the value of the acquisition of student learning motivation after being given treatment is 68.28 and student learning outcomes are 80. Based on the results of the questionnaire given to students and student learning outcomes obtained, it proves that motivation and student learning outcomes in the experimental class are higher than the control class, this is because the experimental class is given treatment using several seating placement models so that students are more motivated and learning outcomes increase during the learning process compared to the control class which only uses a seating management model. conventional or in a row. The significant value is less than 0.05, so it can be concluded that there is an effect of seating management with several models on the motivation and learning outcomes of students in Social Studies subject in Class V at MI Somba Opu District, Gowa Regency. This research is expected that teachers can maximize the management of the main class in terms of student seating management by applying several models to increase student motivation and learning outcomes.